First record of Onuphis eremita (Onuphidae: Annelida) from Buntal Beach, Sarawak, Malaysia - FATIMAH A’TIRAH MOHAMAD; AIMAN AMANINA AMRAN (Society for Indonesian Biodiversity, 2024)
Abstract. Mohamad FA, Amran AA. 2024. First record of Onuphis eremita (Onuphidae: Annelida) from Buntal Beach, Sarawak, Malaysia. Biodiversitas 25: 3768-3774. Since the early 1990s, much research on polychaetes has been conducted across various regions in Malaysia, particularly in Peninsular region, leading to the discovery of numerous new species record. A comprehensive inventory of polychaete species in Malaysia documents records from 1866 to 2013, revealing a total of 57 species in a revised checklist. However, studies focusing on coastal habitats in East Malaysia have been limited, particularly those identifying species at the lowest taxonomic level. This study presents the discovery of a new intertidal species of the family Onuphidae, Onuphis eremita Audouin and Milne- Edwards 1833, which has been newly recorded from South China Sea, specifically in the Buntal Beach, the eastern coast of East Malaysia. The identification is based on the analysis of 19 specimens collected from Buntal Beach, Santubong, Sarawak. These specimens were found in soft sediments characterized primarily by fine sand. Notably, the specimens exhibit large and vividly colored chaetae, which serve as critical identification features. The morphological characteristics of the Malaysian specimens align closely with previous descriptions of O. eremita, confirming their classification. Additionally, the pseudocompound hooks of the specimens display tridentate tips, consistent with earlier descriptions of the species. To enhance understanding, this study includes illustrations and scanning electron microscope (SEM) images of O. eremita, providing valuable visual references for future research. This finding not only contributes to the existing knowledge of polychaete diversity in Malaysia but also highlights the need for further exploration of coastal ecosystems in East Malaysia.